Faith, Culture, and the River: Socio-Religious Dimensions of Waste Disposal Practices in Indonesia - Alimin Alwi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Environmental degradation caused by poor waste management has become an urgent global issue, particularly in rapidly urbanizing cities like Makassar, Indonesia, where rivers have long been treated as natural dumping sites. This research aims to analyze how socio-cultural practices and Islamic religious values shape community behavior in waste disposal along Makassar’s riverbanks. Using a qualitative approach, the research employed in-depth interviews, observation, and documentation to capture the perspectives of residents, community leaders, and religious figures. Data were analyzed through thematic interpretation and triangulated to ensure validity and depth. The findings reveal that waste management behavior is strongly influenced by generational habits and weak social norms, while religious teachings emphasizing cleanliness as part of faith are not consistently translated into environmental action. The study further shows that collaboration between local government and religious institutions can strengthen environmental awareness and transform these values into concrete practices. The implication of this research is that integrating religious ethics with community-based environmental programs can create sustainable behavioral change and enrich sociological discourse on faith-based environmental movements. Degradasi lingkungan akibat pengelolaan sampah yang buruk telah menjadi isu global yang mendesak, terutama di kota-kota yang berkembang pesat seperti Makassar, Indonesia, dimana sungai sejak lama diperlakukan sebagai tempat pembuangan alami. Penelitian ini bertujuan untuk menganalisis bagaimana praktik sosial-budaya dan nilai-nilai keagamaan Islam membentuk perilaku masyarakat dalam isu pembuangan sampah di sepanjang bantaran sungai Makassar. Dengan menggunakan pendekatan kualitatif, penelitian ini dilakukan melalui wawancara mendalam, observasi, dan dokumentasi untuk menggali perspektif warga, tokoh masyarakat, dan pemimpin agama. Data dianalisis secara tematik dan divalidasi melalui triangulasi untuk memastikan kedalaman dan keabsahannya. Temuan penelitian menunjukkan bahwa perilaku pengelolaan sampah sangat dipengaruhi oleh kebiasaan turun-temurun dan lemahnya norma sosial, sementara ajaran agama tentang kebersihan sebagai bagian dari iman belum sepenuhnya diterapkan dalam tindakan lingkungan. Penelitian ini juga menemukan bahwa sinergi antara pemerintah daerah dan institusi keagamaan dapat memperkuat kesadaran lingkungan dan mentransformasikan nilai-nilai tersebut ke dalam praktik nyata. Implikasi penelitian ini adalah bahwa integrasi etika keagamaan dengan program lingkungan berbasis komunitas dapat menciptakan perubahan perilaku yang berkelanjutan serta memperkaya kajian sosiologis tentang gerakan lingkungan berbasis iman.